2016
DOI: 10.1161/circimaging.115.004241
|View full text |Cite
|
Sign up to set email alerts
|

Additive Prognostic Value of Echocardiographic Global Longitudinal and Global Circumferential Strain to Electrocardiographic Criteria in Patients With Heart Failure Undergoing Cardiac Resynchronization Therapy

Abstract: Background-Response to cardiac resynchronization therapy is most favorable in patients with heart failure with QRS duration ≥150 ms and left bundle branch block and less predictable in those with QRS width 120 to 149 ms or non-left bundle branch block. Methods and Results-We studied 205 patients with heart failure referred for cardiac resynchronization therapy with QRS ≥120 ms and ejection fraction ≤35%. We tested the hypothesis that contractile function using speckle-tracking echocardiographic global circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…In an analysis of 313 heart failure patients (non-ischaemic, LBBB) who underwent implantation of a biventricular device, the study showed markedly lower longitudinal strain, suggesting that myocardial dysfunction burden might be the predictor of reverse remodeling in these patients [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis of 313 heart failure patients (non-ischaemic, LBBB) who underwent implantation of a biventricular device, the study showed markedly lower longitudinal strain, suggesting that myocardial dysfunction burden might be the predictor of reverse remodeling in these patients [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…19 In a retrospective series 13 of 205 patients treated with CRT (70% with left bundle branch block QRS morphology), LV GLS <9% was associated with higher rates of all-cause mortality, LV assist device implantation and heart transplantation (unadjusted HR 2.91, 95% CI 1.88-4.49, P<0.001). 20 On multivariate analysis, each decrease in LV GLS was associated with 1.11-fold increased risk of the combined endpoint (95% CI 1.1-1.23, P=0.032).…”
Section: Interaction Between LV Gls and Crtmentioning
confidence: 93%
“…Correct diagnosis and identification of patients with heart failure (HF) is fundamental for their following management, even more when LVEF is preserved. [50][51][52][53][54][55][56] STE has been also applied to heart transplantation 57,58 and to LV assist device (LVAD). 59,60…”
Section: Clini C Al Appli C Ati On Smentioning
confidence: 99%